The Impact of Board of Directors' Independence on Corporate Social Responsibility Disclosure in Palestinian Companies - Omar Tarda; Dato' Hasnah Hj Haron; Supiah Salleh; Nathasa Raml (Usim Press, 2024)
Journal of Muamalat and Islamic Finance Research (JMIFR) Volume 20 No.2 Page (192-204)